Bioinspired total synthesis and structural revision of yuremamine, an alkaloid from the entheogenic plant Mimosa tenuiflora. Issue 28 (10th March 2015) - Calvert, Matthew B.; Sperry, Jonathan
Abstract : A bioinspired synthetic approach to nominal yuremamine has uncovered the true structure of the natural product to be a flavonoidal indole. Abstract : Guided by a biosynthetic hypothesis, a serendipitous total synthesis of yuremamine has resulted in its structural revision from the putative pyrroloindole (1 ) to the flavonoidal indole (2 ), which was initially proposed as a biosynthetic intermediate.